A simple and fast method to determine water content in biodiesel by electrochemical impedance spectroscopy - Delfino, Jose Rodrigues; Pereira, Thulio C.; Costa Viegas, Helmara D.; Marques, Edmar P.; Pupim Ferreira, Antonio A. [UNESP]; Zhang, Lei; Zhang, Jiujun; Brandes Marques, Aldalea L. (Elsevier B.V., 2018)
In this paper, a fast, simple and new alternative method for determination of water content (moisture) in biodiesel using electrochemical impedance spectroscopy (EIS) is developed. The method is based on the sensitive variation of the charge transfer resistance (R-ct) of the biodiesel medium in the presence of different quantities of water. To obtain an accurate analytical measurement, a pre-treatment based on a simple dilution by acetonitrile is employed. The two identical Pt electrodes are used in the measurement cell filled with sample solution. The experiment conditions are also optimized for the measurements. The obtained analytical linear curve between the water content and EIS impedance is the basis for the water content analysis in biodesiel fuel. The EIS method is then successfully applied to both real and certified samples, and the results confirm that the method is reliable with high sensitivity, precision and accuracy. The comparison of EIS method with the official standard method is also made through the Student test t, demonstrating that both methods are statistically consistent and similars. The validation of such an EIS method confirms that the method presented for the fist time in this paper can be succesessfully applied to determining the water content of biodiesel fuel.
Keywords: Water content; Electrochemical impedance spectroscopy; Biodiesel